The growth ring concept: seeking a broader and unambiguous approach covering tropical species - Silva, Marcelo dos S.; Funch, Ligia S.; da Silva, Lazaro B. (Biological reviews of the Cambridge Philosophical Society, 2019)
ABSTRACT The concept of growth rings is little discussed in the literature and their treatment remains somewhat confusing in terms of the diversity of structures described. This situation has a major impact on the study of growth rings in tropical species, in which variations and complexity are greater and accuracy of identification less good. The rigid conceptual delimitations used by dendrochronologists and wood anatomists of temperate regions cannot be applied to the study of growth rings in most tropical species, which has led to neglect of this subject. With the objective of discussing the concept of growth rings, the present study consists of a survey of anatomical, periodicity, causal and evolutionary aspects of the treatment of these structures as evidenced in previous studies, and the evaluation of their application and limitations to the development of this concept. Anatomical aspects arise through radial integrity, or the presence of early and late wood; the degree of distinction of the rings, which may vary from well to poorly defined; and tangential continuity, meaning that rings may form a complete circle in the transverse section of the trunk, or instead be tangentially discontinuous, lens‐shaped or in wedges. In addition there are a diversity of anatomical markers which enable us to recognize growth rings. Regarding periodicity, the rings may be annual, infra‐annual or supra‐annual. Causal aspects include genetic, endogenous and environmental components. Evolutionary aspects continue to be insufficiently investigated, and although most comparative studies treat growth rings recognized by different markers as though they were a single character, it remains questionable whether they can be regarded as homologous or the result of homoplasy. We conclude that the elaboration of a robust but broad definition which can include all the variation observed in growth rings of tropical species is a complex task, which is only possible by overcoming the restrictions adopted by dendrochronologists and wood anatomists of temperate regions for whom growth rings are essentially annual, strongly demarcated, tangentially continuous and restricted to the most pronounced markers.